Resisting gender-based violence in post-1994 South Africa - Dube, Nobuhle Lynn (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
This study investigates the origins of gender-based violence, along with some of the legal, policing, and socio-cultural barriers to effectively addressing gender-based violence in post-1994 South Africa, as perceived and articulated by Black women activists. To that end, this study conducted semi-structured interviews with eight Black South African women activists involved in the fight against GBV, based in different parts of the country. The analysis and the discussion of the research findings are framed around six themes and theorised through an African feminism lens. A key finding of this research project is that GBV in post-1994 South Africa can be attributed to multiple sources which include poverty, African culture, women's liberation in post-1994 South Africa, patriarchy, and toxic masculinities. Another finding of the study is that GBV activists joined the fight against GBV for various reasons, which included personal experience with GBV, a development of feminist consciousness, and a desire to change the justice system and how society understands GBV. A consistent theme in the interviews was that the struggle against GBV is not the sole responsibility of women and girls and that society as a whole bears the responsibility for the fight against GBV. While participants recognised the importance of the compulsory South African high school subject "“ the life orientation syllabus "“ participants pointed out that this subject tends to focus mainly on unplanned teenage pregnancies, the dangers of sexually transmitted diseases, and HIV prevention among young people in South Africa. Thus, the life orientation syllabus foregrounds the dangers of sex, rather than prioritising encouraging students to recognise GBV and equip students with tools to effectively deal with it. Research participants highlighted the importance and benefits of getting involved in the fight against GBV. Participants further recounted that it was the #TheTotalShutDown movement in 2018 that led to President Cyril Ramaphosa meeting with the organisers of #TheTotalShutDown and forming an organising committee, consisting of representatives from the presidency, non-profit groups, and the organisers of #TheTotalShutdown, who worked together to produce the National Strategic Plan against GBV & Femicide which led to the introduction of legislation such as the Domestic Violence Amendment Act 14 of 2022, the Criminal and Related Matters Amendment Act 12 of 2022, and The Criminal Law (Sexual Offences and Related Matters) Amendment Act 13 of 2022.
Keywords: Gender-based violence -- South Africa 1994-; Activism; Social media; Masculinity; Patriarchy; Women Violence against -- South Africa